If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 3(x + -2) = 6 Reorder the terms: 4x + 3(-2 + x) = 6 4x + (-2 * 3 + x * 3) = 6 4x + (-6 + 3x) = 6 Reorder the terms: -6 + 4x + 3x = 6 Combine like terms: 4x + 3x = 7x -6 + 7x = 6 Solving -6 + 7x = 6 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 7x = 6 + 6 Combine like terms: -6 + 6 = 0 0 + 7x = 6 + 6 7x = 6 + 6 Combine like terms: 6 + 6 = 12 7x = 12 Divide each side by '7'. x = 1.714285714 Simplifying x = 1.714285714
| 6x+7=2x+23 | | 10x+3x= | | (8^b/17^a)/(6/7^a) | | x^2=50.4 | | 10=4x-6-3x | | w^2/5/w^4/7 | | 38=2x+2 | | -5-(15Y-1)=2(Y-16)-Y | | 5-(15Y-1)=2(Y-16)-Y | | 6y+20=110 | | 6y+20=21 | | 4(x+4)-11= | | 6y+20=10 | | -8n+4=-4n-12 | | 8x-10=6y+20 | | 2.2q-4.9-1.8q=-0.6q-2.5 | | 0.88889x=56 | | 8x+15=3x-19 | | 8(40-1)-120=11(2U-6) | | x^2=3x-3 | | 0=217+x/(13.2-X)(32.8-X) | | 18xy^3+3xy^2-10xy= | | (3y+1)*25= | | 4(2x+5)=8-3(x+7) | | 4(2x+5)=8-3(x-7) | | 6(y+4)=3(y+1) | | -10n+7=-9n-5 | | 2(4y-1)=6y | | 37x-21+19x=154 | | Bx+Gy=Kforx | | x+3=z-5 | | 217+x/(13.2-X)(32.8-X)=1.25 |